Thar She Blows: Can Bubbles Be Rekindled with Experienced Subjects? - Hussam, Reshmaan N; Porter, David; Smith, Vernon L (American Economic Review, 2008)
We report 28 new experiment sessions consisting of up to three experience levels to examine the robustness of learning and “error” elimination among participants in a laboratory asset market and its effect on price bubbles. Our answer to the title question is: “yes.” We impose a large increase in liquidity and dividend uncertainty to shock the environment of experienced subjects who have converged to equilibrium, and this treatment rekindles a bubble. However, in replications of that same challenging environment across three experience levels, we discover that the environment yields a rare residual tendency to bubble even in the third experience session. Therefore, a caveat must be placed on the effect of twice-experienced subjects in asset markets: in order for price bubbles to be extinguished, the environment in which the participants engage in exchange must be stationary and bounded by a range of parameters. Experience, including possible “error” elimination, is not robust to major new environment changes in determining the characteristics of a price bubble. (JEL C91, D83)